Relying on the Information - TK YAYIN KURULU (Türk Kütüphaneciliği)
The editorial discusses internet filtering in the light of the optional internet packages for users, namely Family, Standard, Kids and Domestic, to be offered by the Information Technologies Board with the "Secure Internet Law" to take effect on August 22, 2011. Also sharing the hesitations about the objectivity of the application with the reader, editorial emphasizes an education system focused on breeding citizens who are not scared of relying on the information and who can, by themselves, decide whether information is harmful or not. References are made to the results of similar applications abroad while the press statement made by Turkish NGOs on the issue are included.